2020
DOI: 10.1039/c9ay02183c
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer analysis by confocal energy dispersive micro-XRD

Abstract: In this work, the confocal energy dispersive micro-XRD technique has been employed to efficiently study differences between normal and malignant carcinomas in breast tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…[11][12][13][14][15] These imaging methods, including energy-dispersive and angular-dispersive raster scanning measurements, coherent scattering computed tomography, and coded aperture systems, seek to measure the XRD signatures of materials throughout a large field of view within reasonable scan times while maintaining adequate spatial resolutions for imaging applications. While simulation studies are often conducted for the design and optimization of these novel imaging architectures, [16][17][18][19] experimental validations on biologically relevant phantoms [20][21][22][23] and real biospecimens 3,6,8,13,15,24 have also occurred. These results have shown that tissues can be differentiated by spatially resolved XRD measurements; however, the resulting rich spatio-spectral datasets necessitate automatic data processing and classification techniques to parse the large data volume.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] These imaging methods, including energy-dispersive and angular-dispersive raster scanning measurements, coherent scattering computed tomography, and coded aperture systems, seek to measure the XRD signatures of materials throughout a large field of view within reasonable scan times while maintaining adequate spatial resolutions for imaging applications. While simulation studies are often conducted for the design and optimization of these novel imaging architectures, [16][17][18][19] experimental validations on biologically relevant phantoms [20][21][22][23] and real biospecimens 3,6,8,13,15,24 have also occurred. These results have shown that tissues can be differentiated by spatially resolved XRD measurements; however, the resulting rich spatio-spectral datasets necessitate automatic data processing and classification techniques to parse the large data volume.…”
Section: Introductionmentioning
confidence: 99%
“…XRD imaging approaches have been developed that seek to circumvent sample preparation, which is often destructive to samples and their spatial correlations, while enabling faster measurements with larger fields of view 11–15 . These imaging methods, including energy‐dispersive and angular‐dispersive raster scanning measurements, coherent scattering computed tomography, and coded aperture systems, seek to measure the XRD signatures of materials throughout a large field of view within reasonable scan times while maintaining adequate spatial resolutions for imaging applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the real texture or ultratexture of HA in bone remains unclear, especially the quantitative texture analysis in three-dimensions, which offers important texture information on biominerals in bones (e.g., no orientation distribution function (ODF) analysis data). As a nondestruction technology, X-ray micro diffractometry (XRMD) has been successfully applied to biomineralization researches, which provides new insight into the crystallographic characteristics of biominerals.…”
Section: Introductionmentioning
confidence: 99%